I've got your number [large type] : a novel - Kinsella, Sophie (Thorndike Press large print basic series., 2012)
Poppy Wyatt has never felt luckier. She is about to marry her ideal man, Magnus Tavish, but in one afternoon her "happily ever after" begins to fall apart. Not only has she lost her engagement ring in a hotel fire drill, but in the panic that follows, her phone is stolen. As she paces the lobby, Poppy spots a phone in a trash can. Finders keepers! Now she can leave a number for the hotel to call when they find her ring. Except the phone's owner doesn't agree.